2017 IEEE Conference on Computer Vision and Pattern Recognition (CVPR) 2017
DOI: 10.1109/cvpr.2017.539
|View full text |Cite
|
Sign up to set email alerts
|

All You Need is Beyond a Good Init: Exploring Better Solution for Training Extremely Deep Convolutional Neural Networks with Orthonormality and Modulation

Abstract: Deep neural network is difficult to train and this predicament becomes worse as the depth increases. The essence of this problem exists in the magnitude of backpropagated errors that will result in gradient vanishing or exploding phenomenon. We show that a variant of regularizer which utilizes orthonormality among different filter banks can alleviate this problem. Moreover, we design a backward error modulation mechanism based on the quasiisometry assumption between two consecutive parametric layers. Equipped … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
124
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 139 publications
(125 citation statements)
references
References 34 publications
1
124
0
Order By: Relevance
“…Recent studies also investigated "softer" orthogonality regularizations by enforcing the Gram matrix of each weight matrix to be close to an identity matrix, under Frobenius norm [38] or spectral norm [39]. We propose a novel spectral value difference orthogonality (SVDO) regularization that directly constrains the conditional number of the Gram matrix.…”
Section: Diversity Via Orthogonalitymentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies also investigated "softer" orthogonality regularizations by enforcing the Gram matrix of each weight matrix to be close to an identity matrix, under Frobenius norm [38] or spectral norm [39]. We propose a novel spectral value difference orthogonality (SVDO) regularization that directly constrains the conditional number of the Gram matrix.…”
Section: Diversity Via Orthogonalitymentioning
confidence: 99%
“…We propose a novel spectral value difference orthogonality (SVDO) regularization that directly constrains the conditional number of the Gram matrix. Also contrasting from [13,38] that apply orthogonality only to CNN weights, we enforce the new regularization on both hidden activations and weights.…”
Section: Diversity Via Orthogonalitymentioning
confidence: 99%
See 1 more Smart Citation
“…Lots of research works have been focusing on learning compact and non-redundant feature descriptors which have many good merits [39], [40], [41], [20], [42], [21]. Chan et al [42] proposed a very simple deep learning framework called PCANet for image classification, which learned orthogonal projection to produce the filters.…”
Section: Compact Feature Learningmentioning
confidence: 99%
“…Chan et al [42] proposed a very simple deep learning framework called PCANet for image classification, which learned orthogonal projection to produce the filters. Xie et al [41] utilized the regularization effect of orthogonalization to improve the classification accuracy. Sun et al [39] quantitatively analyzed the influence of features on person ReID accuracy and found that the associations between different features also impacted the results.…”
Section: Compact Feature Learningmentioning
confidence: 99%